Science of language : interviews with James McGilvray - Chomsky, Noam (Cambridge University Press, 2012)
"Noam Chomsky is one of the most influential thinkers of our time, yet his views are often misunderstood. In this previously unpublished series of interviews, Chomsky discusses his iconoclastic and important ideas concerning language, human nature and politics. In dialogue with James McGilvray, Professor of Philosophy at McGill University, Chomsky takes up a wide variety of topics - the nature of language, the philosophies of language and mind, morality and universality, science and common sense, and the evolution of language. McGilvray's extensive commentary helps make this incisive set of interviews accessible to a variety of readers. The volume is essential reading for those involved in the study of language and mind, as well as anyone with an interest in Chomsky's ideas"--